Influence of different sports on fat mass and lean mass in growing girls - Esther Ubago-Guisado; Esmeralda Mata; Javier Sánchez-Sánchez; María Plaza-Carmona; María Martín-García; Leonor Gallardo (Elsevier, 2017)
Purpose: The aim of this study was to analyze and compare the effects of different sports (swimming, football, basketball, and handball) on fat mass and lean mass in prepubertal and pubertal girls. Methods: Two hundred girls (10.6 ± 1.5 years old, Tanner stages I-III) participated in the study and were divided into 5 groups: 40 swimmers, 40 football players, 40 basketball players, 40 handball players, and 40 controls. Fat and lean masses at whole body, arms, trunk, and legs were measured using dual-energy X-ray absorptiometry (DXA). Pubertal status was determined using Tanner test. Effects of different sports on fat and lean masses were assessed through analysis of covariance with height as covariates. Analyses were performed separately in 2 groups depending on the Tanner stage (prepubertal and pubertal). Results: The girls of the control group had less lean mass and more fat mass compared to the girls who play sports (p < 0.05). There were differences in body fat between sports. The swimmers and football players had less body fat (p < 0.05). On the other hand, handball players showed the highest values in lean mass (p < 0.05). Conclusion: Impact sports (football, basketball, and handball) and low-impact sports (swimming) provide an appropriate development of lean mass in growing girls. We can conclude that people practicing sports at early ages ensure a lower fat mass and higher lean mass compared to those who do not practice. These results may be useful as a preventive method of adult obesity.